Electronic Health Record Adoption and Nurse Reports of Usability and Quality of Care: The Role of Work Environment - Kutney-Lee, Ann; Sloane, Douglas M.; Bowles, Kathryn H.; Burns, Lawton R.; Aiken, Linda H. (Applied Clinical Informatics, 2019)
Background Despite evidence suggesting higher quality and safer care in hospitals with comprehensive electronic health record (EHR) systems, factors related to advanced system usability remain largely unknown, particularly among nurses. Little empirical research has examined sociotechnical factors, such as the work environment, that may shape the relationship between advanced EHR adoption and quality of care.Objective The objective of this study was to examine the independent and joint effects of comprehensive EHR adoption and the hospital work environment on nurse reports of EHR usability and nurse-reported quality of care and safety.Methods This study was a secondary analysis of nurse and hospital survey data. Unadjusted and adjusted logistic regression models were used to assess the relationship between EHR adoption level, work environment, and a set of EHR usability and quality/safety outcomes. The sample included 12,377 nurses working in 353 hospitals.Results In fully adjusted models, comprehensive EHR adoption was associated with lower odds of nurses reporting poor usability outcomes, such as dissatisfaction with the system (odds ratio [OR]: 0.75; 95% confidence interval [CI]: 0.61–0.92). The work environment was associated with all usability outcomes with nurses in better environments being less likely to report negatively. Comprehensive EHRs (OR: 0.83; 95% CI: 0.71–0.96) and better work environments (OR: 0.47; 95% CI: 0.42–0.52) were associated with lower odds of nurses reporting fair/poor quality of care, while poor patient safety grade was associated with the work environment (OR: 0.50; 95% CI: 0.46–0.54), but not EHR adoption level.Conclusion Our findings suggest that adoption of a comprehensive EHR is associated with more positive usability ratings and higher quality of care. We also found that—independent of EHR adoption level—the hospital work environment plays a significant role in how nurses evaluate EHR usability and whether EHRs have their intended effects on improving quality and safety of care.
Keywords: electronic health records; nursing; health care quality; work environment